2022
DOI: 10.3389/fmed.2022.835421
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Secondary Hemophagocytic Lymphohistiocytosis (sHLH) and Candida auris Fungemia in Post-acute COVID-19 Syndrome: A Clinical Challenge

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection causes a disease (COVID-19) with multisystem involvement. The world is now entering a phase of post-COVID-19 manifestations in this pandemic. Secondary hemophagocytic lymphohistiocytosis (sHLH) is a life-threatening hyperinflammatory event triggered by viral infections, including SARS-CoV-2. Both Multisystem Inflammatory Syndrome-Adults (MIS-A) and Cytokine Storm Syndrome (CSS) are considered close differentials of sHLH and add to the spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Persistent or recurrent staphylococcal bacteriaemia related to SD in the COVID-19 pandemic has been reported in other cases of young healthy patients and unapparent infectious foci, speculated to be accounted to the immune disfunction, with secondary (reactive) hemophagocytic lymphohistiocytosis and to the diffuse vascular damages [ 32 , 33 , 34 , 35 ]. The first line of anti-staphylococcal antibiotics aimed highly antibiotic resistant MRSA but resulted in incompletely recovery after six weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent or recurrent staphylococcal bacteriaemia related to SD in the COVID-19 pandemic has been reported in other cases of young healthy patients and unapparent infectious foci, speculated to be accounted to the immune disfunction, with secondary (reactive) hemophagocytic lymphohistiocytosis and to the diffuse vascular damages [ 32 , 33 , 34 , 35 ]. The first line of anti-staphylococcal antibiotics aimed highly antibiotic resistant MRSA but resulted in incompletely recovery after six weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Infections with C. auris have been documented in 45 nations in Far East Asia, the Middle East, Africa, Europe, North America and South America, demonstrating its worrying rapid evolution worldwide [ 9 ]. Moreover, many clinical reports demonstrated that C. auris outbreaks are linked to the COVID-19 pandemic [ 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Fungal Infectionsmentioning
confidence: 99%
“…More studies of these cases are needed to formulate strategies for the diagnosis and management of these novel post-COVID-19 conditions. Meta-analysis studies showed an estimated global prevalence of 5.7% in patients with severe COVID-19 and mortality was estimated at 68% [72].…”
Section: Non-albicans Candida (Nac)mentioning
confidence: 99%